Solar Power IoT Based Smart Agriculture System Using NodeMCU ESP32 - Mohd Khalid, Nur Khairiah; Norezmi Jamal,; Farahiyah Mustafa,; Nor Aira Zambri,; Mohamad Syah Rizal Abdullah, (Progress in Engineering Application and Technology, 2024)
Recent global climatic changes have led to a severe worldwide food shortage, prompting households to address this concern by cultivating sufficient vegetables and crops, as emphasized by the Food and Agriculture Organization of the United Nations (FAO). To tackle the escalating demand for food and energy amid climate change and limited arable land, a proposed controller-based IoT system for greenhouses integrates a solar-based power solution. This system aims to boost efficiency, cut costs, and ensure optimal crop growth irrespective of weather conditions. Utilizing NodeMCU ESP32, data from the DHT11 sensor and soil moisture sensor detect humidity, temperature, and soil moisture, transmitting the information to a Blynk application accessible online. Despite a temporary water tank issue causing data gaps, a high-resolution dataset collected at 15-minute intervals provides crucial insights into greenhouse atmospheric dynamics. The solar-powered system, exhibiting resilience, offers valuable optimization insights. Comparison with Weather Underground data highlights a strong correlation in temperature and humidity, affirming the system's reliability despite limitations in soil moisture data. Future enhancements are suggested to address data gaps and optimize system performance. In conclusion, the integration of solar energy and IoT-driven smart agriculture with NodeMCU ESP32 holds promise for revolutionizing farming, reducing carbon emissions, and enhancing crop management through real-time data access and automated control.